Studi Rancang Bangun Prototipe Kapal Pariwisata Listrik Katamaran Asimetris untuk Penyebrangan Pulau Penyengat sebagai Transportasi Laut Ramah Lingkungan - Adam Adriansyah Putra; Leo Anaris Sakti; Galuh Dea Tiara Shandy; Dimas Saputra; Anggara Setya Dharma (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The need for environmentally friendly marine transportation continues to increase, especially in tourist areas such as Penyengat Island, Tanjungpinang, Riau Islands. In the local context, the design of electric boats has not been widely developed for small islands in Indonesia, even though the potential and urgency for its application is very high. Geographical constraints, limited charging infrastructure, and a lack of technical data are the main obstacles. This research focuses on the design and construction of an electric-powered tourist boat prototype with an asymmetrical catamaran hull type as an effort to support a sustainable transportation system. The boat design applies an asymmetrical catamaran hull configuration to improve sailing stability and energy efficiency. The propulsion system is controlled via a wireless PS2 joystick integrated with an ESP32 microcontroller, supported by a 24V DC motor powered by lithium-ion batteries and solar panels as a supplement. Test results show that the boat can operate stably with remote control, good energy efficiency, and zero emissions during operation. Some technical challenges encountered include limited operational duration due to battery capacity and high sensitivity of electronic components to water exposure. Overall, this prototype has great potential for further development as an environmentally friendly alternative for maritime transportation system. The stable catamaran hull design provides advantages in terms of comfort and safety, especially in calm or shallow waters. The electric propulsion system used has proven to be efficient and responsive, supported by a remote control mechanism that is easy to operate via a wireless joystick